2011
DOI: 10.1097/mca.0b013e328343fbe1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of left ventricular remodeling in patients with STEMI treated with primary PCI

Abstract: The best predictors of remodeling in 6 months' observation have appeared to be lower left ventricular ejection fraction at discharge, poorer perfusion assessed angiographically (MBG scale), and the rate of signal intensity increase reflecting the mean bubble velocity of the myocardium by contrast as assessed by contrast echocardiography. Quantitative perfusion angiography independently has high predictive value for the development of remodeling in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Most, but not all, patients with LVR had STEMI (60%), though NSTEMI diagnosis does not exclude transmural infarction. There are also findings other than LV volume or echocardiographic EF suggesting increased risk of LVR, including: significant diastolic dysfunction [ 20 ], restrictive mitral filling [ 29 ], LV dyssynchrony [ 30 ] and myocardial perfusion in contrast-enhanced echocardiography [ 31 ]. Mitral valve regurgitation is common in patients with MI (15–64%), constitutes an independent risk factor for cardiovascular mortality, and may be a predictive risk factor or even may accelerate LVR [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most, but not all, patients with LVR had STEMI (60%), though NSTEMI diagnosis does not exclude transmural infarction. There are also findings other than LV volume or echocardiographic EF suggesting increased risk of LVR, including: significant diastolic dysfunction [ 20 ], restrictive mitral filling [ 29 ], LV dyssynchrony [ 30 ] and myocardial perfusion in contrast-enhanced echocardiography [ 31 ]. Mitral valve regurgitation is common in patients with MI (15–64%), constitutes an independent risk factor for cardiovascular mortality, and may be a predictive risk factor or even may accelerate LVR [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed studies have shown that up to 25% of patients undergoing angioplasty lack myocardial reperfusion despite revascularization of the infarct-related artery 9. As a result, cardiac mortality remains high, particularly in patients who develop heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative MCE represents a useful tool for the prediction of cardiac remodeling after STEMI [55]. Specifically parameters of contrast intensity (A, , x ) exhibited an excellent sensitivity in predicting heart remodeling within 6-month interval after myocardial infarction.…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%